Aerobic Exercise Affects Vo2 Max in College Students - Septia Triandini; Nurul Aini Rahmawati; Bayu Prastowo (JURNAL KEPERAWATAN DAN FISIOTERAPI (JKF), 2025)
A sedentary lifestyle is a habit of spending more time on immobilization activities such as working in front of a computer, driving, watching television or even participating in social interactions only through social media. This lack of physical activity can have an impact on a person's physical fitness such as a decrease in the maximum oxygen volume capacity. (Vo2 max) this decrease is an indicator to assess a person's cardiorespiratory fitness, a sedentary lifestyle has a high risk of various health problems including cardiovascular disease, so it is important to increase physical activity to maintain fitness and increase (Vo2 max). The general objective of this study was to determine the effect of Aerobic Exercise on (Vo2 max) in students. This research method uses a Quasi Experimental approach with a one group pre-test and post-test design for respondents in students who meet the inclusion and exclusion criteria, respondents are given jogging exercises 12 times in 1 month and they are measured using the Multistage Fitness Test or Bleep Test to determine (Vo2 max). The results based on the Wilcoxon test show a p-value = 0.001 <0.05 which means there is an influence between variables on (Vo2 max). The conclusion is that there is an increase (Vo2 max) in students after being given aerobic exercise which was given 12 times in 1 month.